If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -7w + 2y + 5w + 4x + 8y = 0 Reorder the terms: -7w + 5w + 6x + 4x + 2y + 8y = 0 Combine like terms: -7w + 5w = -2w -2w + 6x + 4x + 2y + 8y = 0 Combine like terms: 6x + 4x = 10x -2w + 10x + 2y + 8y = 0 Combine like terms: 2y + 8y = 10y -2w + 10x + 10y = 0 Solving -2w + 10x + 10y = 0 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-10x' to each side of the equation. -2w + 10x + -10x + 10y = 0 + -10x Combine like terms: 10x + -10x = 0 -2w + 0 + 10y = 0 + -10x -2w + 10y = 0 + -10x Remove the zero: -2w + 10y = -10x Add '-10y' to each side of the equation. -2w + 10y + -10y = -10x + -10y Combine like terms: 10y + -10y = 0 -2w + 0 = -10x + -10y -2w = -10x + -10y Divide each side by '-2'. w = 5x + 5y Simplifying w = 5x + 5y
| n=20*2 | | 10x^2-10x+7=0 | | 3x^5-5x^4+17x^3=31x^2-28x+28 | | 6f+3M= | | 4v^2-28v=0 | | 2n*20= | | log(3)x+log(3)x+4=log(3)x+10 | | 4b^2-23b+15=0 | | 3x-7=44 | | 10c^2+11c-6=0 | | -4x*1x= | | -4x(x-5)= | | 20x+1=5x-6x | | 12x^2+116x-204=0 | | 8x+6x^2=15x+3x^2 | | 26-3g=8 | | (3i+2j)(7i+9j)= | | 56=-28n | | x+2=3(82-x) | | 3(x+1)(x+1)-(x+3)(2x+2)=0 | | 7x-2=7x+28 | | 8-6x=14-7 | | -8y+32=5-7y | | (x+4)(x+4)-(3x-7)(3x-7)=0 | | 6x+27=-38+47 | | 1.5x-0.33x+0.33+4x+8=180 | | Pi*49= | | ln(x+2)+ln(2x+2)=ln(40) | | ln(x+2)+ln(2x+2)= | | 3(v+8)-5v=14 | | 7(-3y+2)=3(8+7y) | | 6a+b=-3 |